Impacts des structures rigides de protection sur la côte néo-brunswickoise de la baie des Chaleurs au Canada - Simon Diouf; Dominique Bérubé; André Robichaud (VertigO)
Hard coastal defences (HCD) have multiplied in the last few decades on the Chaleur Regional Service Commission area, a situation that requires the assessment of their effects on coastal processes and features. In this study, photogrammetric techniques were used to make an accurate appraisal of impacts. Firstly, historical coastline change was measured for two periods: 1934-1985 and 1985-2012/2018. Secondly, beach surface occupied by HCD was quantified. Finally, topographic surveys on beach morphology were carried out. Results show that HCD represent 54 % of the study area coastline. The hardened sections of the coastline become fixed, while adjacent natural sections globally an accelerated retreat. HCD cover 23 % of beaches in Nigadoo, 12 % in Beresford, 37 % in Salmon Beach west and 27 % in Salmon Beach Est. Finally, it was found that the hardened beaches are on average two to four times less wide than natural beaches and present the lowest foreshore elevations.